PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF COURSE REVIEW HORAY DENGAN PEMBELAJARAN KONVENSIONAL PADA MATA PELAJARAN EKONOMI SISWA KELAS X SMA ADABIAH PADANG (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2013)
The research was motivated by the low student learning outcomes. This is evident from the second semester exams MID economic subjects class X SMA ADABIAH Padang school year 2012/2013. This study aims to look at differences in student learning outcomes using learning model hooray Review Course with conventional learning in class X SMA ADABIAH Padang. This type of research is the study of the subject with a random experiment. The population in this study were all students of class X SMA ADABIAH Padang enrolled in the school year 2012/2013 which consists of 9 classes. Sampling was done by purposive sampling technique and was chosen as the experimental class is the class X2 and X3 Control class. Instrument used is the final test form a valid objective and reliable = 0.76 at 95% confidence interval. Classroom learning with the experimental results on average 74.5 higher than the control class with an average 64.6. Based on the data analysis it could be concluded that There is a difference Student Results Using cooperative learning model hooray Review Course With Conventional Learning Lesson In Economics Class X High School ADABIAH Padang.